2011
DOI: 10.2478/s11536-011-0104-3
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of secretory IgA in human breast milk and stool samples after the intake of a probiotic — report of 2 cases

Abstract: AbstractOnly a few studies reveal immunological changes in breast milk after the intake of probiotic and none focus on secretory IgA (sIgA). The aim our report was to investigate the levels of sIgA in human breast milk and stools before and after 4 weeks of probiotic intake in a patient with ulcerative colitis (UC) and a control. The study included 2 lactating women: 1 with UC and 1 control. Both received daily 3.75 billion viable Lactobacillus bulgaricus for 28 days. SIgA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It has to be considered that there exist some results including data in between the above-established periods, thus making the organization of data more difficult. IgA in colostrum is quantified in samples from the first day of production, considered by some authors as day 0 [45,[70][71][72][73] or day 1 [74][75][76][77]. Some studies collected samples on other specific days during this milk period: on day 2 [72,78], on day 3 [45,79,81], on day 4 [41,59,76], or on day 5 [77,81,83].…”
Section: Iga Concentration In Breast Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…It has to be considered that there exist some results including data in between the above-established periods, thus making the organization of data more difficult. IgA in colostrum is quantified in samples from the first day of production, considered by some authors as day 0 [45,[70][71][72][73] or day 1 [74][75][76][77]. Some studies collected samples on other specific days during this milk period: on day 2 [72,78], on day 3 [45,79,81], on day 4 [41,59,76], or on day 5 [77,81,83].…”
Section: Iga Concentration In Breast Milkmentioning
confidence: 99%
“…The concentration of IgA in this period is quite variable, as commented on in a previous section. Only 11 of the 60 types of samples included (18%) provided values under the 1 g/L, and although some of them are derived from just one mother [34,73] or in particular situations, such as cow's milk allergy (CMA) or ulcerative colitis (UC) [73,79,85], others involved healthy women [77,81]. Most of the studies show values of between 1 and 10 g/L, specifically in 43 of the 60 populations studied (72%, Table 1).…”
Section: Iga Concentration In Breast Milkmentioning
confidence: 99%
“…It was found that the expression level of JCHAIN in spleen and rectum was relatively high, but in thymus was relatively low [20]. Previous studies have shown that after lactating women ingested daily viable Lactobacillus bulgaricus for 28 days [21], probiotics activate the lymphocytes and synthesize IgA dimers with J-chain, which increased SIgA content in both breast milk and feces obviously. In present study, JCHAIN expression in the spleen of broilers was highly significantly increased after feeding Bacillus cereus PAS38, which may play an important role in the expression of downstream cytokines, thus affecting the immunity of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have studied the expression level of JCHAIN in adult chicken brain, intestine, thymus, spleen, bursa of fabricius and other tissues and organs, and found that the expression level in spleen and rectum was higher, while the expression level in thymus is lower [20]. In addition, some studies have shown that Lactobacillus bulgaricus can activate lymphocytes, synthesize IgA dimer through JCHAIN, and significantly increase the level of sIgA in breast milk and feces of lactating women [21]. In this experiment, the expression of JCHAIN in the immune organs of broilers increased significantly after feeding Bacillus cereus, which may be a positive signal for the immunity of broilers.…”
Section: Plos Onementioning
confidence: 99%